<span>-7 • (a4 - 81a2 - 162)27
-------------------------------- hope it helps
27</span>
Ay^2+2ay-3a
a(y^2+2y-3)
a(y-1)(y+3)
The full cost would be £33.75
Yes it is (10x-y)^2 is the answer of it
<h3>
Answer:</h3>
y = (x +2)(x -1)(x -3) . . . . or . . . . y = x³ -2x² -5x +6
<h3>
Step-by-step explanation:</h3>
The graph shows y=0 at x=-2, x=1, and x=3. These are called the "zeros" or "roots" of the function, because the value of the function is zero there.
When "a" is a zero of a polynomial function, (x -a) is a factor. This means the factors of the graphed function are (x -(-2)), (x -1) and (x -3). The function can be written as the product of these factors:
... y = (x +2)(x -1)(x -3) . . . . . the equation represented by the graph
Or, the product can be multiplied out
... y = (x +2)(x² -4x +3)
... y = x³ -2x² -5x +6 . . . . . the equation represented by the graph